Strengthening Strengthening the Islamic Identity of Students through ODOS2 (One Day One Short Surah) Religious Habituation Program - Munawar, Fuad; Safwandy Nugraha, Mulyawan; Nursobah, Asep (Al-Ishlah: Jurnal Pendidikan Islam, 2024)
Islamic religion is enriched with various teachings, including brief verses in the Qur'an that contain the values of faith and Islam. To integrate this, strategies are needed to strengthen the religious identity of students that can help them gain a deeper understanding of the religious teachings and values they adhere to with religious habituation programs. The purpose of this study is to explain the ODOS2 (one day one short surah) religious habituation program and contribute further understanding regarding the effectiveness of religious habituation methods in increasing students' understanding of Islamic religious teachings in the ODOS2 (one day one short surah) method. This research is qualitative with a case study approach to see the reality of ODOS2 (one day one short surah) religious habituation activities carried out at SMA IT Asy-Syakur as a superior religious habituation program. The source of this research data was sourced from religious habituation activities of students at SMA IT Asy-Syakur and scientific articles relevant to the research focus. Data were collected through observation, interview, and documentation studies. There are many religious habituation programs implemented in every school that have become redundant. One of the religious habituation programs that can be applied in schools to strengthen Islamic identity is the ODOS2 (one day one short surah) religious habituation program implemented at Asy-Syakur IT High School. The program is proven to strengthen the Islamic identity of students.